2001
DOI: 10.1108/02621710110388956
|View full text |Cite
|
Sign up to set email alerts
|

Women, equality and construction

Abstract: Examines the situation faced by women in the UK construction industry. Finds that women are confronted by a significant number of barriers, beginning with difficulties in joining the industry. In addition, the administrative or human resource management roles traditionally occupied by women do not lead to mainstream roles and senior management roles. To increase prospects, women need to able to take on the more mainstream roles in the industry such as design, engineering and construcition iteself. The main inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 1 publication
2
49
0
Order By: Relevance
“…This study showed that recruiting was routinely done through informal and personal sources putting women at a disadvantage. As an example, the CITB advertises for its training courses at football matches, which tend to be watched more heavily by males (Fielden, Davidson, Gale, & Davey, 2001). A manager confided that he felt threatened by women coming into the industry (Greed, 2000).…”
Section: Barriers To Women In Construction Management Programs 241mentioning
confidence: 97%
See 1 more Smart Citation
“…This study showed that recruiting was routinely done through informal and personal sources putting women at a disadvantage. As an example, the CITB advertises for its training courses at football matches, which tend to be watched more heavily by males (Fielden, Davidson, Gale, & Davey, 2001). A manager confided that he felt threatened by women coming into the industry (Greed, 2000).…”
Section: Barriers To Women In Construction Management Programs 241mentioning
confidence: 97%
“…This was confirmed by Menches and Abraham (2007) that life and family issues strongly influence a women's career paths. In a survey of men and women working in construction, all participants felt that flexible hours and access to childcare would increase the opportunities for women in the construction industry (Fielden, Davidson, Gale, & Davey, 2001).…”
Section: Barriers To Women In Construction Management Programs 241mentioning
confidence: 99%
“…According to Fielden et al (2001), contractors discriminate against women. This discrimination is based on the assumption that women go on maternity leave, making them unreliable and present a greater possibility of conflicts because of their family responsibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Higgin et al (2000) contend that women still carry the primary responsibility for domestic duties in most households. Therefore, males are preferred for construction work, and females are underrepresented in the construction industry (Arditi and Balci, 2009;Dainty et al, 2000;Fielden et al, 2001;Byrne et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation